Association between Rosacea and Risk Factors - A Literature Review - Furgalska-Kudła, Julia; Suława, Adrian; Targoński, Oskar; Targońska, Marta; Fedorowicz, Sebastian; Basiak, Aneta; Ptasiński, Aleksander; Niekurzak, Rafał; Buczek, Agnieszka (Quality in Sport, 2024)
Introduction and purpose: Rosacea is a common chronic inflammatory disease with four clinical subtypes based on the predominant signs and symptoms. The majority of patients present skin problems like reddening, papules or pustules, swelling of the face and nose, and eye symptoms like dryness, tearing, and redness. Anxiety and depression associated with rosacea deeply affect the quality of patients’ lives. Yet, the pathogenesis of rosacea remains poorly understood, with suggestions of involvement from various complex factors like immune dysregulation, genetic factors, neurovascular dysregulation, micro-organisms, and environmental factors as promoting features of rosacea. Aim of the study: The purpose of this article is to investigate the association between factors like alcohol intake, Helicobacter pylori infection, and cardiovascular diseases and the risk of developing rosacea. Material and methods: An analysis of papers available in PubMed, Google Scholar, and Springer Link was performed. Conclusion: The knowledge presented in this review suggests the existence of links between rosacea and various risk factors like alcohol intake, infection of H.pylori, and Cardiovascular diseases. Considering the clinical and pathological differences among rosacea subtypes, it is essential to explore the role of alcohol in each subtype separately. While rosacea may not be directly associated with IHD, stroke, or diabetes, it does show correlations with hypertension and dyslipidemia. Rosacea is significantly associated with a higher prevalence of HP infection, but high-quality prospective studies are needed to ascertain if Helicobacter Pylori is a risk factor for rosacea. Further investigations are warranted to validate these findings and explore underlying mechanisms. The predisposing factors revealed in this study could help us gain insights into rosacea pathophysiology and develop interventions especially targeting modifiable risk factors.